2022
DOI: 10.3389/fgene.2022.933862
|View full text |Cite
|
Sign up to set email alerts
|

INHBB is a novel prognostic biomarker and correlated with immune infiltrates in gastric cancer

Abstract: Inhibin subunit beta B (INHBB) is a potential prognostic biomarker for a variety of cancers. However, its role in gastric cancer (GC) remains elusive. The differential expression data of INHBB in tumor and normal tissues were extracted from several databases and genetic alterations of INHBB were assessed by cBioPortal. Kaplan-Meier analysis was used to evaluate the survival rate of patients with GC with INHBB and association with clinical features in GC. Cox regression analysis was used to explore the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Despite this, a large number of studies have demonstrated elevated INHBB expression in rectal cancer, endometrial cancer, adrenocortical carcinoma, oral squamous cell carcinoma, and placental tumor ( 28 , 31 , 32 ). In this study, we discovered that high INHBB expression was associated with a poor prognosis in patients with bladder cancer; similar findings have been reported in other study on gastric cancer ( 33 ). KLF12 is a member of the Krüppel-like factors (KLFs) family ( 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…Despite this, a large number of studies have demonstrated elevated INHBB expression in rectal cancer, endometrial cancer, adrenocortical carcinoma, oral squamous cell carcinoma, and placental tumor ( 28 , 31 , 32 ). In this study, we discovered that high INHBB expression was associated with a poor prognosis in patients with bladder cancer; similar findings have been reported in other study on gastric cancer ( 33 ). KLF12 is a member of the Krüppel-like factors (KLFs) family ( 34 ).…”
Section: Discussionsupporting
confidence: 90%
“…Among them, INHBB is a member of the transforming growth factor β superfamily, which has been identified as a potential prognostic biomarker in various cancers including CRC. 66 , 67 We also found that INHBB was highly expressed in CRC, but the expression trend lacked necessary experimental verification and was only predicted by bioinformatics analysis. SNAI1 is a critical EMT inducer and a driving factor for cancer progression, including cell invasion, survival, immune regulation, stemness, and metabolic regulation.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, a recent study showed that active fractions from golden-flowered tea dropped INHBB expression in tumor cells of non-small cell lung cancer. 27 Combined with the finding from immune infiltration result in gastric cancer 20 and immunocompromised patients via deep learning in OSCC, 28 it is suggested that tumor immune microenvironment may play a role in INHBB modulation. After unraveling the mystery of the regulatory mechanism of INHBB in oral cancer, it would help develop possibly specific anticancer drugs.…”
Section: Discussionmentioning
confidence: 96%
“… 18 , 19 A similar result has been found in gastric cancer, where INHBB was correlated with immune infiltration. 20 Furthermore, INHBB provided an environment suitable for metastasis of hepatocellular carcinoma. 21 Conversely, other studies in the epigenetic field held a contrary opinion.…”
Section: Introductionmentioning
confidence: 99%